Feasibility of modulation-encoded TOBE CMUTS for real-time 3-D imaging - Chee, Ryan K. W.; Zemp, Roger J. (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2015)
Modulation-encoded top orthogonal to bottom electrode (TOBE) capacitive micromachined ultrasound transducers (CMUTs) are proposed 2-D ultrasound transducer arrays that could allow 3-D images to be acquired in a single acquisition using only N channels for an N × N array. In the proposed modulation-encoding scheme, columns are not only biased, but also modulated with a different frequency for each column. The modulation frequencies are higher than the passband of the CMUT membranes and mix nonlinearly in CMUT cells with acoustic signals to produce acoustic signal sidebands around the modulation carriers in the frequency domain. Thus, signals from elements along a row may be read out simultaneously via frequency-domain multiplexing. We present the theory and feasibility data behind modulation-encoded TOBE CMUTs. We also present experiments showing necessary modifications to the current TOBE design that would allow for crosstalk-mitigated modulation-encoding.